Infective endocarditis due to nasal septal perforation during home oxygen therapy - Kyota Shinfuku; Naoki Takasaka; Ryutaro Ohashi; Taiki Fukuda; Makiko Takatsuka; Ryo Sato; Mitsuyoshi Mita; Tsukasa Hasegawa; Masami Yamada; Yumie Yamanaka; Yusuke Hosaka; Kai Ryu; et al. (Respirology Case Reports, 2024)
Abstract We report a case of infective endocarditis (IE) due to nasal septal perforation during Home oxygen therapy (HOT). A 64‐year‐old man with a history of interstitial pneumonia (IP) and on HOT was hospitalized for dyspnea. Methicillin‐sensitive Staphylococcus aureus (MSSA) was repeatedly detected in blood cultures. Echocardiography revealed tricuspid valve vegetation and regurgitation. The patient was diagnosed with IE, according to the modified Duke criteria. A full‐body examination revealed nasal septal perforation and MSSA was isolated from the nasal cavity. The patient was treated with cefazolin and clindamycin. However, he developed aspiration pneumonia and subsequently died. The portal of entry of MSSA was damaged nasal mucosa, caused by dryness and curettage of the dried nasal mucus during HOT. Nasal septal perforation, a potential complication of HOT, may cause severe bacterial infections. Consequently, diligent nasal care is crucial during HOT.